Extrapulmonary and disseminated tuberculosis in HIV-1-seropositive patients presenting to the acute medical services in Nairobi. - Gilks, C; Brindle, R; Otieno, L; Bhatt, S; Newnham, R; Simani, P; Lule, G; Okelo, G; Watkins, WM; Waiyaki, P (1990)
We studied 506 consecutive adult acute medical admissions to hospital in Nairobi; 95 (18.8%) were seropositive for HIV-1, and 43 new cases of active tuberculosis (TB) were identified. TB was clearly associated with HIV infection, occurring in 17.9% of seropositive patients compared with 6.3% of seronegatives [odds ratio (OR) 3.2; 95% confidence limits (CL) 1.6-6.5]. Extrapulmonary disease was more common in seropositive than seronegative TB patients (nine out of 17 versus five out of 26; OR 4.7; 95% CL 1.01-23.6); this accounted for most of the excess cases of TB seen in seropositive patients. Mycobacteraemia was demonstrated in two of eight seropositive TB patients but in none of 11 seronegative TB patients. No atypical mycobacteria were isolated. The World Health Organization (WHO) clinical case definition for African AIDS did not discriminate well between seropositive and seronegative TB cases. Five out of seven seropositive women with active tuberculosis had delivered children in the preceding 6 months and were lactating, compared with only one out of eight seronegative tuberculous women. An association between recent childbirth, HIV immunosuppression and the development of TB is suggested.